SYNTHESIS OF CHALCONE AND PYRAZOLINE DERIVATIVES WITH ACETOPHENONE AND VERATRALDEHYDE AS PRECURSORS - Fatmayanti, Baiq Risma; Habibie, Ahmad; Dhey, Anselmania Kartini (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Chalcones and pyrazolines are heterocyclic compounds with promising biological and pharmaceutical activities. Chalcone and pyrazoline can be found in different sources, such as natural and synthetic compounds. This study aimed to explore the synthesis of chalcone and pyrazoline derivatives with acetophenone and veratraldehyde as precursors. Chalcone was successfully synthesized through the Claissen-Schmidt reaction between acetophenone and veratraldehyde at room temperature 25-30 ºC and mediated by KOH as a base catalyst for 20 hours. The corresponding substituted pyrazoline derivative was also successfully synthesized through a cyclocondensation reaction between the synthesized chalcone and phenylhydrazine as starting materials under reflux conditions at temperatures of 75-80 ºC for 4 hours. The Chalcone A derivative compound obtained was (E)-3-(3,4-dimethoxy phenyl)-1-phenyl prop-2-en-1-one (Chalcone A). The Pyrazoline A derivative compound was obtained as pyrazole compound 5-(3,4-dimethoxy phenyl)-1,3-diphenyl-4,5-dihydro-1H-pyrazole (pyrazoline A). Chalcone A and Pyrazoline A obtained as yellowish and brownish-orange powders in 14.89 % and 66.57 % yields, respectively. The chastities of Chalcone A and Pyrazoline A was 98.55 % and 88.54 %, respectively. A qualitative identification for both synthesized compounds was performed using normal-phase thin-layer chromatography which revealed the Rf value for Chalcone A and Pyrazoline A was 0.43 (in mobile phase ethyl acetate:n-hexane 3:1 v/v) and 0.55 (in mobile phase DCM:n-hexane 3:1 v/v), respectively. Moreover, the elucidation structure of synthesized compounds using FTIR and GC-MS instruments revealed the structure of synthesized Chalcone A and Pyrazoline A agrees with the theoretical structure of Chalcone A and Pyrazoline A. Keywords: Synthesis, Chalcone, Pyrazoline, Acetophenone, Veratraldehyde